THE EFFECT OF DYNAMIC EXPLOSIVE POWER EXERCISES ON THE SPEED AND STRENGTH OF LEG MUSCLES AND SHOOTING ACCURACY OF FOOTBALL PLAYERS - Dr. Yasser Jaafar Abdullah (Scholars Digest Publishing, 2025)
The current research aims to study the effect of dynamic explosive power exercises on the speed and strength of leg muscles and shooting accuracy of football players, in order to evaluate the effectiveness of these exercises in developing the players' physical and technical abilities. The researcher adopted a two-group experimental design (experimental and control) as it was chosen as the most suitable for measuring the effect of the training program on variables without direct intervention that would affect the natural conditions of the research population. The research population was identified purposively and consisted of players from second-division clubs in the Iraqi league for the 2025-2026 sports season. The research sample consisted of 23 players from Al-Khalis Sports Club. After random drawing, 10 players were selected for the experimental group and 10 players for the control group, with 3 goalkeepers statistically excluded. Th expletory sample of 3 players was formed to test the research instruments and ensure their clarity and validity. The research results showed that applying dynamic explosive power exercises contributed significantly to improving the strength and speed of leg muscles and shooting accuracy of the players, which confirms the effectiveness of these exercises in developing physical and technical performance. Based on this, the researcher recommends the necessity of including dynamic explosive power exercises in the training program. As part of the regular training programs for football players to enhance muscle strength, speed, technical accuracy and achieve the best performance for the players.
Keywords: Dynamic explosive power exercises, speed, strength, shooting accuracy in football.